Pre-Service Teacher’s Attitude during Study at the Institute of Teacher Education Based on Al-Zarnuji Thought - Wan Hamat, Wan Hasmah Laili; Hamzah , Mohd Isa; Zulkifli, Hafizhah (International Journal of Psychosocial Rehabilitation, 2020)
Student teachers will be the determinants of future education of the country and it is important for them to absorb positive attitudes while learning. Constant attitude changes to a better direction are very important. Therefore, this study aimed to elaborate on the attitude towards learning based on Al-Zarnuji's thought which should be a practice and also to identify the current attitude among the students. The study used the methods of literature review and survey using questionnaires to obtain data. The data obtained were analyzed descriptively. A total of 30 teachers from the Central Zone Teacher Education Institute were randomly selected as respondents of the study. The findings showed that items ‘came early to the class’ (Mean = 4.20, sd = .610) and ’focus during the lectures’ (Mean = 4.20, sp = .664) were the highest while the lowest learning attitudes was ‘reviewing the lesson as soon as the class was over’ (Mean = 3.50, sd = .861). The overall level of attitude of the students during the learning were at the moderately high level (Mean = 3.93, sd = .584) which meant that they demonstrated a positive attitude in acquiring knowledge as suggested by Al-Zarnuji. Al-Zarnuji's method of learning as a practice among student teachers should be widely disseminated and applied so that the student teachers produced are not only knowledgeable and skilled, but also have a positive attitude and wisely adapting to any change.